1978
DOI: 10.1111/j.1440-6055.1977.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SENSORY NERVOUS SYSTEM OF THE ADULT CATTLE TICK BOOPHILUS MICROPLUS (CANESTRINI) IXODIDAE. PART III. ULTRA‐STRUCTURE AND ELECTROPHYSIOLOGY OF CHELICERAL RECEPTORS

Abstract: Departniiwf c!f Entomology, U t i i w r s i t j~ (f Q u i w dotid> St Lirciu. Austruliu. 4067. AbstractThe inner and the outer cheliceral digits of the cattle tick B. niicroplus have been investigated with transmission electron microscopy and found to be innervated by sensory neurones. The outer digit has a terminal papilla innervated by two neurones which appear to be mechanoreceptors and two sensory pits, one pit innervated by eleven neurones some of which are chenioreceptors, and the other pit by a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The localization and morphology of most of the sensory receptors involved in feeding behaviour and the ultrastructures of tick neurons has been studied, but not at the transcriptome level [11,12,61]. The difference in the gene expression patterns between B. taurus and B. indicus frustrated larvae compared to unfed larvae could be a result of differences in host specific stimuli during the larval attachment phase on these breeds.…”
Section: Resultsmentioning
confidence: 99%
“…The localization and morphology of most of the sensory receptors involved in feeding behaviour and the ultrastructures of tick neurons has been studied, but not at the transcriptome level [11,12,61]. The difference in the gene expression patterns between B. taurus and B. indicus frustrated larvae compared to unfed larvae could be a result of differences in host specific stimuli during the larval attachment phase on these breeds.…”
Section: Resultsmentioning
confidence: 99%
“…Waladde and Rice (1977) suggested that the resistant animals might present substances on the skin or in the serum, that when perceived by gustatory sensilla may inhibit the conclusion of the blood meal by the tick, been related as much in the selection of the host, as in the manifestation of the host resistance. Aside from this supposition, we are aware of no other reports confirming this idea.…”
Section: Discussionmentioning
confidence: 98%
“…Rhipicephalus evertsi evertsi and Rhipicephalus appendiculatus, two species of ticks that parasitize bovines, are capable of differentiating preferential sites of attachment on the same host, through chemical substances (Wanzala et al 2004). Waladde and Rice (1977) suggested that the resistant animals present substances on the skin or in the serum, that when perceived by gustatory sensilla, inhibit the conclusion of a blood meal by the tick, in this way contributing to the selection of the host, and thus in the manifestation of resistance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Taste receptors are present in the distal segment of the palps and chelicerae, and the tip of tarsus I on the legs. These taste receptors detect non-volatile compounds (WALADDE & RICE, 1977;WALADDE, 1982;WALADDE & RICE, 1982;TAYLOR et al, 1991;GRENACHER et al, 2001;SOARES et al, 2013;FERREIRA et al, 2015). Ticks integrate the sensory information received by olfactory and taste receptors and transmit these to the synganglion, which is the tick's central nervous system.…”
Section: Introductionmentioning
confidence: 99%